Spectrum of Nondiabetic Kidney Diseases in Patients with Type 2 Diabetes Mellitus Who Underwent Kidney Biopsy in Egypt - Salem Kaawele; Ahmed Elkeraie; Eman Youssef; Mohamed Elrggal; Mahmoud Elrggal; Rowan Zyada; Wessam Esmail (Karger Publishers, 2024)
Introduction: Diabetic kidney disease (DKD) affects 30-40% of patients with diabetes. The prevalence of nondiabetic kidney disease (NDKD) in patients with type 2 diabetes mellitus (T2D) in Egypt is unknown. This study aimed to assess the prevalence of NDKD in patients with T2D in Egypt. Methods: In this cross-sectional study, we searched the data of patients with T2D who underwent a native kidney biopsy between January 2010 and December 2020 in a kidney pathology laboratory in Egypt. Results: Of 12,006 patients who underwent kidney biopsy, 677 patients had T2D. NDKD was found in 285 patients (42.7%), DKD in 220 patients (33%), and mixed DKD and NDKD in 162 patients (24.3%). The total prevalence of NDKD was 67% in patients with T2D in our study group. Membranous nephropathy was the most common histopathological disease in patients with NDKD (20.6%) followed by acute tubular injury (ATI) (19.2%) and focal segmental glomerulosclerosis (15.2%). The presence of ATI in a kidney biopsy was associated with a significantly higher mean serum creatine level (p < 0.001). Minimal change disease was associated with a significantly higher proteinuria level (p < 0.001). In binary logistic regression analysis, combining NDKD and mixed groups, the duration of diabetes was a negative predictor of NDKD, with a longer duration decreasing the likelihood of NDKD. Conclusion: NDKD is prevalent among patients with T2D who underwent a kidney biopsy. Kidney biopsy remains the gold standard for diagnosing NDKD in patients with T2D.